al-Maadah al-Ta'liimiyyah ala Asaasi al-Huqul al-Dilaaliyyah fi Ta'liimi al-Arobiyyah - Maimuna Maimuna; Edy Murdani Z (Lugawiyyat, 2022)
AbstractIslamic of Junior High school (MTs) Bina Islam Uses Some books for teaching Arabic language Such as: Terampil berbahasa Arab and exercise book of Fasih berbahasa Arab. Meanwhile, both books give more priority target to upgrade the Reading Capable of Students and Also the Chapters explain materials globally and don’t detail. Speaking skills was one of more important aims in study of a foreign language and seems to be a main goal that every teacher has to upgrade it. And it wouldn’t come true when they never prepare a good material and use a good method in their teaching activity. Based on those statements, the researcher wish to design a materials instruction intended to improve the student’s Arabic speaking skills and competency. This research used quantitative approach and the type of this research was a kind of “Research and Development” (RD). The purposes of this research are: 1) product handbook to improve student’s Arabic speaking skill with Semantic Approach 2) the effective test of handbook in improving student’s Arabic speaking skill of (MTs) Bina Islam Tanah Grogot East Kalimantan The results of this research are: 1) product handbook to improve student’s Arabic speaking skill with Semantic Approach, 2) the experiment appointed that using product handbook could improve the ability of students to speak Arabic. There are suggestions for the school and it’s Arabic teachers: 1) rearrange the material of Arabic lesson, especially Arabic speaking skill, based on need analysis 2) avoid the use of mother tongue when teaching Arabic speaking, because it makes the students get used to translate the lesson or explained in the mother tongue 3) the teaching materials designed for Arabic speaking skill with Semantic Approach is a tool of important tools in the teaching process that can benefit the Arabic teachers of Madrasah Tsanawiyah Bina Islam Tanah Grogot or other Islamic Junior high school.الكلمات الأساسية: المواد العليمية ، الحقل الدلالي، مهارة الكلام